Kebijakan Pemerintah Untuk Mengatasi Masalah Pengangguran di Indonesia Pasca Pandemi Covid -19 - Elsaviya, Firani Anan; Sari, Ikko Dea Abdul Fatika (CV. Civiliza Publishing, 2023)
Introduction: The Covid-19 pandemic has significantly impacted the world economy, one of which is the economy in Indonesia. The Indonesian economy is increasingly experiencing a decline, and poverty and unemployment are increasing. This research aims to analyze government policies to overcome the problem of unemployment in Indonesia after Covid 19. Research Methods: The method used in this research is to use a descriptive qualitative approach with library research. Results: The research results show that the government has implemented policies to overcome the unemployment problem in Indonesia post-Covid-19, as follows: (1) Allocating funds for handling Covid-19. (2) Organizing income tax incentive programs and relaxing credit payments. (3) Provide social assistance to 70.5 million informal sector workers in the vulnerable and poor categories. (4) Organizing various competency and productivity-based trainings. (5) Expanding job opportunities for workers affected by the pandemic. (6) Opening of consultation, information, and complaint services for workers related to Occupational Safety and Health. (7) Issuance of Pre-Employment Cards to develop competency and job opportunities. Conclusion: The government has implemented the right policies to overcome the unemployment problem in Indonesia after Covid-19.